Clinical Trial Outsourcing: India's Regulatory Landscape. - Mukherjee, Anasua (2009)
Abstract: Clinical Trials are a part of the global pharmaceutical value chain that are strategically outsourced to low cost emerging locations across the world, such as Eastern Europe, Latin America and Asia. India boasts of a well-developed pharmaceutical market and has several location advantages that lure multinational pharmaceutical companies to outsource clinical trial operations to its market. Post 2005, the regulatory frameworks controlling drug trials on human subjects have also improved to add to India’s location advantages. In the wake of declining productivity and increased cost-pressures, pharmaceutical companies are trying to locate their outsourcing activities to countries that offer cheap resources and also have an internationally standardized regulatory framework, so that trial results of drugs tested in those locations are accepted by the US-FDA for approval. FDA approvals are condition to ethical conduct and GCP compliance of trials. The Indian guidelines for GCP and ethical trials are internationally standardized and most trial data produced from the Indian site is acceptable by the US-FDA for approval evaluations of the tested drug. This has substantially added to the location-advantage of the Indian Clinical Trial Market.